A Novel Boost-SEPIC based Three-Port DC-DC Converter for Solar PV Integrated E-Boat Applications - Ruhela A.; Chinmaya K.A. (My University, 2025)
This paper deals with the design and development of a novel Boost-SEPIC based three-port converter (TPC). The developed converter is used as a DC microgrid in electric boat consisting of roof-top solar PV (SPV) panels. This proposed converter is capable of managing the energy supplied by solar PV and battery, and delivering a continuous power to the load. The proposed TPC comprises of two parts, first part is capable of detecting the MPP(maximum power point), while the second part is the integration of SPV and battery with load using the Boost-SEPIC converter. It eliminates the need of three different DCDC converters for charging, discharging, and continuous power supply to the load. It has many advantages such as compact design, whole control over load voltage and low ripple currents during the transient time.Boost-SEPIC TPC can swiftly change between different modes of operation by detecting the load variations, Battery SOC, and PV availability, thereby ensuring continuous power flow towards the load. The system topology is designed and analyzed using the simulated results in the Matlab-SIMULINK environment. And the results depicting the continuous power flow to the load in different modes of operation have been presented. Thus proving the viability of the proposed converter. © 2022 IEEE.